PERAN KOMPETENSI DAN INDEPENDENSI AUDITOR DALAM MENINGKATKAN KUALITAS AUDIT KEUANGAN NEGARA - NOR, WAHYUDIN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011), 2011)
The act No. 15/2006 is concerned with the Audit Board of the Republic of Indonesia (BPK RI), while its authority refers to the article 9 (1). In performing its duties, BPK RI has an authority to recruit experts and/or external auditors that work on behalf of BPK RI. This act provides a great opportunity for motivated external auditors to audit state financial institution. To have a better knowledge of the audit bid in the government sector, it is important to understand external auditors’ opinion about their motivation in pursuing audit engagement of government audit market. However, the auditor’s motivation to pursue government audit market engagement would have an impact on audit quality. Good quality of audits requires both competency and independency. These qualities have direct effects on actual audit quality, as well as potential interactive effects. In addition, financial statement users’ perception of audit quality is a function of their perceptions of both competency and independency. This article explains competency and independency that influence audit quality if audit process in conducted by external auditor.
Keywords: external auditor, competence, independence, audit quality